Vesicular release of glutamate utilizes the proton gradient between the vesicle and synaptic cleft - Brown, Jon T.; Weatherall, Kate L.; Corria, Laura R.; Chater, Thomas E.; Isaac, John; Marrion, Neil V. (Frontiers in Synaptic Neuroscience, 2010)
Glutamate is released from synaptic vesicles following formation of a fusion pore, connecting the vesicle interior with the synaptic cleft. Release is proposed to result from either full fusion of the vesicle with the terminal membrane or by ‘kiss-and-run’, where release occurs through the fusion pore. ‘Kiss-and-run’ seems implausible as passive diffusion of glutamate through the pore is too slow to account for the rapidity of release. Vesicular accumulation of glutamate is driven by a proton gradient, resulting in the co-release of protons during exocytosis. We tested whether the proton gradient between the vesicle and cleft contributes to glutamate exocytosis. Collapse of the gradient reduced hippocampal glutamatergic transmission, an effect that was not associated with presynaptic changes in excitability, transmitter release probability, or postsynaptic sensitivity. These data indicate that approximately half of glutamate release utilizes the proton gradient between vesicle and cleft, suggesting a significant proportion of release by ‘kiss-and-run’.